Stability and welfare effects of profit taxes within an evolutionary market interaction model - Noemi Schmitt; Jan Tuinstra; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
We develop a partial equilibrium model in which firms can locate in two separate regions. A firm's decision where to locate in a given period depends on the regions' relative profitability. If firms react strongly to the regions' relative profitability, their market switching behavior generates unstable dynamics. If the goal of policy makers is to stabilize these dynamics they can do so by introducing profit taxes that reduce the regions' relative profitability. While stability can already be obtained by imposing profit taxes in one of the two regions, total welfare is maximized if policy makers coordinate their tax setting behavior across regions. However, policy makers only interested in welfare in their own region may have the incentive to decrease their profit tax below this level, thereby attracting more firms and increasing tax revenues, at the cost of instability in both regions.
Keywords: D83; E30; H20; 330; market interactions; evolutionary dynamics; profit taxes; policy coordination; welfare effects; stability analysis